Electrical and electrochemical properties of double-decker Lu(III) and Eu(III) phthalocyanines with four imidazoles and N-alkylated imidazoles - ÖZKAYA, ALİ RIZA; DUMLUDAĞ, FATİH (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Imidazole tetrasubstituted double-decker Lu(III) (2) and Eu(III) (3) phthalocyanines have been synthesized by heating 4[(4,5-diphenyl-1H-imidazole)-2-yl-thio]phthalonitrile (1) with Lu(OAc)(3)center dot nH(2)O or Eu(OAc)(3)center dot nH(2)O in n-hexanol in the presence of 1,8-diazabicyclo[5.4.0]undec-7-ene, respectively. N-alkylated imidazole tetrasubstituted double-decker Lu(III) (4) and Eu(III) (5) phthalocyanines have been synthesized by the reaction of compounds 2 and 3 with hexyl bromide, in DMF in the presence of K2CO3, respectively. The new compounds were obtained in sufficient purity after successive washing with different solvents and were characterized by elemental analysis and H-1 NMR, UV-Vis, IR, MALDI-TOF mass and electron spin resonance spectra. Electrical measurements of the 2-5 performed in a vacuum (<2 x 10(-3) mbar) in the dark between the temperatures of 295 and 523 K suggest that their films show semi-conductor behavior. It was found that, in general, sigma(d.c.) (4) > sigma(d.c.) (2) in the temperature range 295-458 K, and sigma(d.c). (5) > sigma(d.c.) (3) in the measured temperature range. Depressed semi-circles with different radii at high temperatures in impedance spectra measurements indicated deviation from the Debye dispersion relation. The redox behaviors of the compounds were also investigated by voltammetry and in situ spectroelectrochemistry in dimethylsulfoxide with tetrabutylammonium perchlorate. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Imidazole; Double-decker phthalocyanines; Lanthanide; Electrical properties; Electrochemistry; GAS-SENSING PROPERTIES; CRYSTAL-STRUCTURES; ACTIVATION-ENERGY; AC CONDUCTION; COMPLEXES; METAL; BIS(PHTHALOCYANINATO); ABSORPTION; ZN(II); SUBSTITUENTS